Analisis Pelaksanaan Program Kampung Organik Di Kota Magelang Melalui Model MSN-Approach (Studi Kasus Kampung Organik Sari Makmur) - Lufthansa Hilwa Nugraha; Fadlurrahman; Nugraha, Joko Tri Nugraha; Tri Asih Wismaningtyas, (Sawala : Jurnal Administrasi Negara, 2024)
The Organic Village Program is an innovation program of Magelang City in overcoming waste and food security problems that has been established since 2013. However, the number of organic villages in Magelang city has decreased. This study aims to analyze the implementation of the Organic Village Program in Magelang city through the MSN-Approach model. The method used is a qualitative method with a case study approach. Data collection techniques include interviews, observations, and documentation. Informants in this study are the Department of Environment, Department of Agriculture and food, facilitators, administrators and members of Sari Makmur Organic Village. The data analysis used by Miles, Huberman, and Saldana is an interactive data analysis model consisting of data condensation, data presentation, and conclusion. The results of the study indicate that the implementation of the Organic Village Program is quite good. In the mentality approach, the government has been supportive and proactive. Meanwhile, in the participants, there was a decrease in the responsibility of carrying out daily pickets. In the system approach, including regulation, cultural values and organizational structure and functions are good. In the networking approach, including aspects of strategic partnership, synergy, and mutualistic symbiosis are quite good, the obstacle lies in synergy where the skills of participants in this program are still limited.